2020
DOI: 10.1212/wnl.0000000000009014
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-specific white matter reductions in Parkinson hallucinations and visual dysfunction

Abstract: ObjectiveTo investigate the microstructural and macrostructural white matter changes that accompany visual hallucinations and low visual performance in Parkinson disease, a risk factor for Parkinson dementia.MethodsWe performed fixel-based analysis, a novel technique that provides metrics of specific fiber-bundle populations within a voxel (or fixel). Diffusion MRI data were acquired from patients with Parkinson disease (n = 105, of whom 34 were low visual performers and 19 were hallucinators) and age-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 50 publications
8
70
0
Order By: Relevance
“…PD low visual performers showed significant changes in white matter macro-and micro-structure compared to PD high visual performers, longitudinally ( Figure 3) and already at baseline ( Figure 4A), as we have shown previously 13 . At baseline, PD low visual performers showed reduction in FC within the splenium of the corpus callosum, the right cingulum and bilateral posterior thalamic radiation.…”
Section: ) Baseline Changes In White Matter Micro-structure and Macrsupporting
confidence: 82%
See 4 more Smart Citations
“…PD low visual performers showed significant changes in white matter macro-and micro-structure compared to PD high visual performers, longitudinally ( Figure 3) and already at baseline ( Figure 4A), as we have shown previously 13 . At baseline, PD low visual performers showed reduction in FC within the splenium of the corpus callosum, the right cingulum and bilateral posterior thalamic radiation.…”
Section: ) Baseline Changes In White Matter Micro-structure and Macrsupporting
confidence: 82%
“…Performance in these tasks have been shown to correlate with cognitive but not lowlevel visual performance at baseline as well as worsening cognition at one-year follow up 5,17 . We have also shown that task performance is associated with fibre-specific white matter changes 13 .…”
Section: Methodsmentioning
confidence: 71%
See 3 more Smart Citations